AB1122 Effects of Proprioceptive Exercises in Rheumatoid Arthritis Postmenopausal Women: GAIT Biomechanical Parameters Related with Falls, Functional Capacity and Disease Activity (Preliminary Results). (10th June 2014) - Aleixo, P.; Simões, E.; Roupa, I.; Coelho, P.; Vaz Patto, J.; Abrantes, J.
Abstract : Background: Rheumatoid arthritis (RA) patients 1 and postmenopausal women 2 showed an increased fall risk. Research pointed to some gait biomechanical parameters related with falls (GBPRF) 3 and found differences in these parameters between elderly and young: elderly showed higher ratio of head to hip horizontal acceleration and higher heel horizontal velocity at heel contact with the ground 3 ; elderly and young showed similar minimum toe clearance values however elders had greater variability. 4 There is strong evidence that balance and coordination exercises (proprioceptive exercises, PE) can reduce fall rates in elderly. 5 Objectives: Analyze the PE effects in RA postmenopausal women relatively to disease activity, functional capacity and GBPRF. Methods: RA postmenopausal women (n=7) participated in a 12-week PE individual program (3 sessions/week, 30 minutes/session). Data collected pre and post-program. DAS28 and HAQ used to evaluate disease activity and functional capacity. Vicon® Motion Capture system recorded kinematics data (9 MX1.3 cameras, 200Hz) synchronized with a force plate (AMTI BP400600-200, 1000Hz). Data analyzed by Vicon® Nexus software (1.7.1) based on an integrated model of 41 reflective markers relocation and subject anthropometric data, developing mechanical segments and joints centers. Subjects performed 14 valid trials (7 left and 7 right foot contacts with AMTI). Results: Improvements in HAQ (1.00 to 0.46, t student, p=0.005) and visual analogue scale for pain (4.95 to 2.07 cm, t student, p=0.003). DAS28 results remained statistical unchanged (4.32 to 3.54, t student, p=0.127). GBPRF did not show statistical differences ( t student, p<0.05): left and right heel antero-posterior velocity (0.35 to 0.30 m/s, p=0.310; 0.30 to 0.28, p=0.604; respectively); left and right minimum toe clearance (2.07 to 1.86 cm, p=0.113; 1.94 to 1.87 cm, p=0.468); head antero-posterior velocity/hip antero-posterior velocity at 4 crucial gait instants (left heel contact - 0.85 to 0.87, p=0.440; right heel contact - 0.87 to 0.88, p=0.369; left minimum toe clearance - 1.08 to 1.06, p=0.168; right minimum toe clearance - 1.10 to 1.05, p=0.309; left contralateral heel contact - 0.88 to 0.87, p=0.367; right contralateral heel contact - 0.86 to 0.86, p=0.829; left toe off - 1.03 to 1.03, p=0.862; right toe off - 1.00 to 1.02, p=0.588). Conclusions: Despite the small number of participants data indicate that PE can improve functional capacity and reduce pain perception in RA postmenopausal women. In addition did not exacerbate disease activity. GBPRF did not show pre and post-program differences however a larger sample may allow observation of differences accompanying observed improvements in functional capacity. References: Hayashibara M, Hagino H, Katagiri H, Okada J, Teshima R. Osteoporosis International 2010;21(11):1825–1833 Cangussu L, Nahas-Neto J, Nahas E, Barral A, Buttros D, Uemura G. BMC Musculoskeletal Disorders. 2012;13:2 Winter D. The Biomechanics and motor control of human gait: normal, elderly and pathological. 2nd ed. Waterloo: University of Waterloo Press; 1991:87–94 Barrett R, Mills P, Begg R. Gait & Posture 2010;32(4):429–435 Sherrington C, Whitney J, Lord S, Herbert R, Cumming R, Close J. Journal of the American Geriatrics Society 2008;56:2234–43 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3890